The development of arable weed vegetation according to the arable land use and plant migrations in Central-Europe from the Neolithic to the new times - Pinke, Gyula (JOURNAL OF LANDSCAPE ECOLOGY, 2005)
This paper mainly based on archaeobotanical finds reviews the development of the Central-European arable weed vegetation from the Neolithic to the new times. During the shifting cultivation in the prehistoric times, there were almost exclusively apophytes weeds on the fields. In the Roman periods greatly increased the immigration of Mediterranean elements. By the medieval two- or three-field rotation system the significance of annuals became higher, but the perennials still also played a great role. Some of our classical weeds gained mass occurrences in that time. In the new times the crops from the New World changed the traditional farming systems, and neophytes started their expansions.
Keywords: weed species; weed vegetation; archeobotany